2019
DOI: 10.1158/1078-0432.ccr-17-3852
|View full text |Cite
|
Sign up to set email alerts
|

SMAC Mimetic Debio 1143 and Ablative Radiation Therapy Synergize to Enhance Antitumor Immunity against Lung Cancer

Abstract: Purpose: Adaptive antitumor immunity following ablative radiotherapy (ART) is attenuated by host myeloid-derived suppressor cell (MDSC), tumor-associated macrophage (TAM), and regulatory T-cell (Treg) infiltrates. We hypothesized treatment with ART and a secondary mitochondrialderived activators of caspase (SMAC) mimetic could reverse the immunosuppressive lung cancer microenvironment to favor adaptive immunity.Experimental Design: To evaluate for synergy between ART and the SMAC mimetic Debio 1143 and the dep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Our study builds upon these prior findings by showing that ASTX660 can induce expression of classic ICD markers in sensitive cell lines in vitro, suggesting that this mechanism of anti-tumor immunity is intact for a subset of HNSCC tumors. Another study showed synergistic anti-tumor immunity when combining IAP antagonist Debio 1143 with XRT in lung cancer models, 48 a relationship that Figure 4. ASTX660 enhances TIL-mediated killing of HNSCC cell lines.…”
Section: Discussionmentioning
confidence: 94%
“…Our study builds upon these prior findings by showing that ASTX660 can induce expression of classic ICD markers in sensitive cell lines in vitro, suggesting that this mechanism of anti-tumor immunity is intact for a subset of HNSCC tumors. Another study showed synergistic anti-tumor immunity when combining IAP antagonist Debio 1143 with XRT in lung cancer models, 48 a relationship that Figure 4. ASTX660 enhances TIL-mediated killing of HNSCC cell lines.…”
Section: Discussionmentioning
confidence: 94%
“…IAP inhibition has attracted extensive attention over the last decade. With the in‐depth study of IAP functional sites, the antitumor and radiosensitizing effects of Smac and its mimetics have become an important research focus …”
Section: Discussionmentioning
confidence: 99%
“…In addition, APG-1387 could induce tumor cell death and enhance innate antitumor immunity in HBV-positive hepatocellular carcinoma with a high expression of cIAP2 and stimulate adaptive immunity in vitro by reducing Treg differentiation and PD-1 expression [ 158 ]. The SMAC mimic Debio 1143 enhanced tumor-specific adaptive immunity induced by ablation radiotherapy [ 208 ]. In addition, IAP antagonists could significantly improve the antitumor effects of cells or other immune agents in combination therapy, including chimeric antigen receptor (CAR) T-cells, cytokine-induced killer cells, NKT cell inducers α-GalCer, TNF-α, and PD-1 blockade [ 13 ].…”
Section: Therapeutic Targeting Of E3 Ligases In Cancer Immunotherapymentioning
confidence: 99%